Atopic diseases and airway-related symptoms in Bavarian children before starting primary school: Time trend analyses. (January 2022) - Pirner, Christina; Korbely, Christine; Heinze, Stefanie; Huß, Jonas; Summer, Burkhard; Oppel, Eva; Nowak, Dennis; Herr, Caroline; Kutzora, Susanne; ,; Doerk, Wiltrud; Pfister, Angelika; et al.
Abstract: Background: After decades of rising prevalence of atopic and airway-related diseases, studies showed stagnating prevalence in western industrialised countries. Objective of this study is to analyse the time trend of prevalence of atopic diseases and airway-related symptoms among Bavarian children before starting primary school. Materials and methods: Five cross-sectional studies from 2004/2005, 2006/2007, 2012/2013, 2014/2015 and 2016/2017 took place in urban and rural regions in Bavaria, Germany. Using standardized parent questionnaires children's atopic diseases and airway-related symptoms were surveyed. Logistic regression analysis (Bonferroni correction: adjusted significance level 0.005) was performed to analyse prevalence of symptoms and diseases from 2004 to 2017 for time trends. Results: The surveys included 27384 Bavarian children aged 5–6 years (52.6% male). In all children the calculated 12-month prevalence of symptoms '≥four episodes of wheeze' (p-value = .0880) and 'rhinoconjunctivitis' (p-value = .3994) reported by parents stagnated, whereas 'wheeze' (p-value<.0001; OR = 0.97; CI = [0.96–0.98]) and 'rhinitis' (p-value = .0007; OR = 0.98; CI = [0.97–0.99]) decreased. In all children the calculated lifetime prevalence of physician-diagnosed 'asthma' (p-value = .5337), and 'hay fever' (p-value = .8206) stagnated, whereas of 'bronchitis' (p-value<.0001; OR = 0.98; CI = [0.98–0.99]) decreased over time. The calculated lifetime prevalence of physician-diagnosed 'atopic eczema' (p-value = .0002; OR = 0.98; CI = [0.97–0.99]) decreased in all children, whereas the calculated 12-month prevalence of the symptom 'itchy rash' increased (p-value = .0033; OR = 1.07; CI = [1.05–1.08]) over time. Conclusions: Several calculated prevalence of children's atopic diseases and airway-related symptoms reported by parents stagnated in a subgroup of Bavarian children before starting primary school between 2004 and 2017. The time trend of prevalence in 'wheeze', 'rhinitis' and 'bronchitis' decreased. Prevalence of 'atopic eczema' decreased over time, whereas 'itchy rash' increased. Highlights: Some atopic and respiratory conditions stagnated over time in Bavarian children before starting primary school. Less of these children had 12-month wheeze and rhinitis in 2004 compared to 2017 according to parent reported assessments. Lifetime bronchitis and atopic eczema decreased in Bavarian children before starting primary school. Monitoring should be ensured because of serious effects for affected children and health system.